A Numerical Proof of Concept for Thermal Flow Control - Dragan, V. (Engineering, Technology & Applied Science Research, 2017)
In this paper computational fluid dynamics is used to provide a proof of concept for controlled flow separation using thermal wall interactions with the velocity boundary layer. A 3D case study is presented, using a transition modeling Shear Stress Transport turbulence model. The highly loaded single slot flap airfoil was chosen to be representative for a light aircraft and the flow conditions were modeled after a typical landing speed. In the baseline case, adiabatic walls were considered while in the separation control case, the top surface of the flaps was heated to 500 K. This heating lead to flow separation on the flaps and a significant alteration of the flow pattern across all the elements of the wing. The findings indicate that this control method has potential, with implications in both aeronautical as well as sports and civil engineering applications.